Critical Factors Affect to Project Management - Hidayat, Rachmad; Zusi, H (Universitas Mercu Buana, 2020)
This research is designed to analyze critical success factors which consisted of support of top management, the contribution of project management, implementation of education and training, user involvement in the success of ERP system implementation at PT. EDS Manufacturing Indonesia. The research method used is multiple linear regression analysis using questionnaire distribution. The population was the company employees, with 59 respondents being used as samples. The sampling method is purposive sampling, which was taken from various strata in the company that is actively involved in the implementation and use of the ERP system. The hypothesis testing was carried out using a validity test, reliability test, t-test, and F-test as well as quantitative descriptive analysis. Data was obtained by using a questionnaire instrument containing a list of statements to measure respondents according to research variables. The results indicate that partially, the contribution of project management has a significant effect on the success of ERP systems implementation. While the support of top management, implementation of education and training and user involvement does not have a significant effect on the success of ERP system implementation. All critical factors success can explain their relationship to the success of ERP system implementation by 31.0%.